2010
DOI: 10.1007/s11433-010-3218-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of the CN stretching mode of [Ru(CN)6]4− in D2O studied by nonlinear infrared spectroscopy

Abstract: We have studied vibrational dynamics of the T 1u mode of the CN stretching mode of [Ru(CN) 6 ] 4− in D 2 O by infrared (IR) nonlinear spectroscopy such as an IR three-pulse photon echo experiment and polarization-sensitive IR pump-probe spectroscopy. The isotropic component of the pump-probe signal shows a bi-exponential decay with time constants of 0.8 ps and 20.8 ps. The fast and slow components correspond to the rapid equilibration between the T 1u mode and the Raman active modes of the CN stretching mode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The role of electric field fluctuations in the dephasing dynamics of charged species dissolved in polar solvents has been widely studied to understand the role of solvent fluctuations in chemistry and biology. There is growing experimental evidence that the collective dynamics of the solvent around small ionic solutes play the biggest role in determining the amplitudes and time scales of the vibrational frequency fluctuations of the solute. ,, Tominaga and co-workers have performed systematic studies of measuring the FFCFs of the cyanide, nitrosyl, and azide stretching vibrations in ionic solutes dissolved in aqueous solvents. ,, Their studies find a common time scale ranging from 1 to 1.5 ps for the frequency fluctuations for various ions regardless of the vibration being studied. This similar time scale has been obtained in experimental studies of the OH(OD) stretch of HOD in D 2 O(H 2 O). ,,, Molecular dynamics simulations have been used to obtain the FFCF of the azide stretch in D 2 O and the OH(OD) stretch of HOD in D 2 O(H 2 O). ,, The simulation studies have shown that the experimentally measured picosecond vibrational dephasing dynamics are driven by electric field fluctuations originating from collective reorganization of the hydrogen bonding network.…”
Section: Discussionmentioning
confidence: 99%
“…The role of electric field fluctuations in the dephasing dynamics of charged species dissolved in polar solvents has been widely studied to understand the role of solvent fluctuations in chemistry and biology. There is growing experimental evidence that the collective dynamics of the solvent around small ionic solutes play the biggest role in determining the amplitudes and time scales of the vibrational frequency fluctuations of the solute. ,, Tominaga and co-workers have performed systematic studies of measuring the FFCFs of the cyanide, nitrosyl, and azide stretching vibrations in ionic solutes dissolved in aqueous solvents. ,, Their studies find a common time scale ranging from 1 to 1.5 ps for the frequency fluctuations for various ions regardless of the vibration being studied. This similar time scale has been obtained in experimental studies of the OH(OD) stretch of HOD in D 2 O(H 2 O). ,,, Molecular dynamics simulations have been used to obtain the FFCF of the azide stretch in D 2 O and the OH(OD) stretch of HOD in D 2 O(H 2 O). ,, The simulation studies have shown that the experimentally measured picosecond vibrational dephasing dynamics are driven by electric field fluctuations originating from collective reorganization of the hydrogen bonding network.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamical quantities were investigated by the pump–probe or transient grating technique in the IR region, which are also third-order nonlinear techniques. In Table , we summarize the results from the FTIR measurements of the probe molecule together with those of the population relaxation and orientational relaxation for methanol and aqueous solutions at room temperature. The results for the temperature dependence on N 3 – in aqueous solutions can be found in ref .…”
Section: Three-pulse Ir Photon Echo Experiments In Aqueous Solutionsmentioning
confidence: 99%
“…We have studied the vibrational frequency fluctuation of probes, such as triatomic ions and metal complexes with CN or NO ligands, in various hydrogen-bonding solvents, including water droplets in reverse micelles. The concentrations of the solutes were 20–60 mM, which are low enough to ensure that the solvation shells do not overlap. Figure a shows the three-pulse IR photon echo signals of N 3 – in D 2 O at 303 K under all-parallel polarization conditions.…”
Section: Three-pulse Ir Photon Echo Experiments In Aqueous Solutionsmentioning
confidence: 99%
“…3 Furthermore, we have studied the spectral diffusion processes of the antisymmetric stretching modes of OCN À and SCN À in methanol, and the CN stretching modes of metal complexes in water by using three-pulse IR photon echo methods. [28][29][30][31][32] We have recently reported a detailed analysis of the temperature dependence of the vibrational dynamics of azide in water. 33 In addition to studies of simple ion-solvent systems, the antisymmetric stretching modes of azide and thiocyanate have attracted much attention because these modes are useful IR probes for studying the fluctuations of the surrounding environment in peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%